TEACHER APPROACH IN INCULCATING DISCIPLINE ATTITUDES IN THE FOURTH GRADE STUDENTS AT SDN PATOKAN 2 DISTRICT TAHUN 2017 - Dodik Eko Yulianto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2017)
This study aims to determine the approach of teachers using behavior modification and in planting student discipline attitude. the title proposed in this study is "Master's Approach in Inculcating Discipline Attitudes in Class IV Students". This research was conducted at SDN 2 Patokan Situbondo Regency. This research uses qualitative research method, using behavior modification approach method. Behavior modification refers to behavioral change techniques, such as changing a person's behavior and reactions to a stimulus through strengthening adaptive behavior and / or the elimination of maladaptive behavior through an affectionate approach to each student so that they are comfortable with the school situation and the teacher will more easily provide advice to students so students will also easily receive the advice of teachers without ignoring it .. Modification of this behavior is to provide motivation to students and attitude changes, this approach can provide motivation that leads to good so that students are able to control himself, so that each individual is not considered bad by others, because having a high discipline attitude will show the quality of life. discipline as a provision for students to navigate their future lives, The forms of discipline in SDN 2 Patokan Situbondo in question is the discipline of students present to the school, discipline students in doing the task, discipline students in school lessons, discipline in dress and discipline in shaking hands with the teacher. While performing the teaching tasks of teachers applying classroom management techniques so that students can be disciplined, the techniques used are advice, reprimands, manners, orders and rewards. This technique is used for the learning process can take place conducively and know the various character of all discipline students that have been done well so that SDN 2 Patokan Situbondo become a superior school in Situbondo regency